Project Management – Identification of Variables That Impact Project Success in Australian Organizations - Harcz, Csaba (Digital Repository of Theses, 2025)
The main objective of my dissertation work is, to examine different aspects of the project success criteria (requirements, standards) and success factors (circumstances, facts and influences) at different organizations in Australia that can influence the success of a project. As a result of my dissertation work, I would like to help the leaders, project managers, and project members by giving them a comprehensive picture of the aspects of the current situation and with this help, to make projects more effective and more successful in the future. My dissertation work will present a literature review that contains the introduction to projects, project management, the different applicable leadership styles, success factors, and success criteria. During the empirical study, I used quantitative data collection as the primary research methodology. In other words, I used a survey to reveal those elements that influence the success of projects. Processing the results of the research, it has been established that the positions of project members are different, but regarding both success factors and success criteria, the same element could be revealed. As a consequence of the assumption that differences can be detected in the opinions related to various positions, it was rejected. The impact of greater service years at the examined Australian companies on success factors and success criteria was also studied. The result of this research did not confirm this assumption either. Based on the research results, suggestions have been made for further research directions in the future. Comprehensive research with a larger number of elements can prove the correctness of the questions and assumptions formulated during my research. It can also identify research directions that can be used to evaluate a project more accurately, whether it is successful or failed.